Participation and performance trends in ultracycling - Abou Shoak M; Knechtle B; Knechtle P; Rüst CA; Rosemann T; Lepers R (Dove Medical Press, 2013)
Mohannad Abou Shoak,1 Beat Knechtle,1,2 Patrizia Knechtle,2 Christoph Alexander Rüst,1 Thomas Rosemann,1 Romuald Lepers31Institute of General Practice and Health Services Research, University of Zurich, Zurich, Switzerland; 2Gesundheitszentrum St Gallen, St Gallen, Switzerland; 3INSERM U1093, Faculty of Sport Sciences, University of Burgundy, Dijon, FranceBackground: Participation and performance trends have been investigated in ultramarathons and ultratriathlons but not in ultracycling. The aim of the present study was to investigate (1) participation and performance trends in ultraendurance cyclists, (2) changes in cycling speed over the years, and (3) the age of the fastest male and female ultraendurance cyclists.Methods: Participation and performance trends in the 5000 km Race Across America (RAAM) and in two RAAM-qualifier races – the 818 km Furnace Creek 508 in the United States and the 715 km Swiss Cycling Marathon in Europe – were investigated using linear regression analyses and analyses of variance.Results: On average, ~41% of participants did not finish either the RAAM or the Furnace Creek 508, whereas ~26% did not finish the Swiss Cycling Marathon. Female finishers accounted for ~11% in both the RAAM and the Furnace Creek 508 but only ~3% in the Swiss Cycling Marathon. The mean cycling speed of all finishers remained unchanged during the studied periods. The winner’s average speed was faster for men than for women in the RAAM (22.6 ± 1.1 km · h-1 versus 18.4 ± 1.7 km · h-1, respectively; average speed difference between male and female winners, 25.0% ± 11.9%), the Swiss Cycling Marathon (30.8 ± 0.8 km · h-1 versus 24.4 ± 1.9 km · h-1, respectively; average speed difference between male and female winners, 27.8% ± 9.4%), and the Furnace Creek 508 (27.4 ± 1.6 km · h-1 versus 23.4 ± 3.0 km · h-1, respectively; average speed difference between male and female winners, 18.4% ± 13.9%). In both the Furnace Creek 508 and the Swiss Cycling Marathon, ~46% of the finishers were aged between 35 and 49 years. The mean age of winners, both male and female, across the years in the Furnace Creek 508 and in the Swiss Cycling Marathon was 37 ± 10 years.Conclusion: These findings in ultracycling races showed that (1) ~26%–40% of starters were unable to finish, (2) the percentage of female finishers was ~3%–11%, (3) the gender difference in performance was ~18%–28%, and (4) ~46% of the successful finishers were master athletes. Future studies need to investigate the reasons for the low female participation and focus on the age-related performance decline in other ultraendurance events in order to confirm that master athletes are predisposed to ultraendurance performances.Keywords: ultraendurance, finisher, speed, gender difference, master athlete, cycling